2020
DOI: 10.3390/jmmp4020060
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Detection of Geometric- and Weight-Related FSW Tool Wear Using Stripe Light Projection

Abstract: Friction stir welding (FSW) has become an up-and-coming joining method with a wide range of industrial applications. Besides the unique weld seam properties, recent investigations have focused on the process-related tool wear of shoulder and probe, which can have detrimental economic and technological effects. This paper presents a systematic quantitative characterization of FSW tool wear using stripe light projection as a novel method to detect weight and form deviations of shoulder and probe. The investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A maximum temperature of 590°C was measured in the SZ. Studies from previous work by Hasieber et al 7 show comparable maximum temperatures of 585.6°C for measurements in the tool. In addition, it could be shown that the temperature in the initial state and after a weld length of 80 m are approximately similar for the welding parameters and tool dimensions used.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…A maximum temperature of 590°C was measured in the SZ. Studies from previous work by Hasieber et al 7 show comparable maximum temperatures of 585.6°C for measurements in the tool. In addition, it could be shown that the temperature in the initial state and after a weld length of 80 m are approximately similar for the welding parameters and tool dimensions used.…”
Section: Resultsmentioning
confidence: 52%
“…The thermo-mechanical stresses and tribological interactions on the tool thereby lead to changes in the shape of the shoulder and probe. 7,12 As a result, the geometric-related FSW tool wear has been shown to cause varying material flow conditions, lateral path deviations and premature tool failure under certain circumstances with detrimental economic and technological consequences. 7 Preventive wear measures such as coatings 13 or the use of hard metals 14 can consequently help to increase tool life - and thus process efficiency - and to reduce machine downtimes due to FSW tool wear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the FSW process, the joining temperatures are below the material's solidus curve so that weld seam irregularities such as pores and hot cracks may be prevented due to the absence of a melting bath [3][4][5]. But FSW is simultaneously affected by process related challenges such as high process forces, tool wear, and comparative low welding speeds [6][7][8]. Hence economical aspects such as high costs for large FSW setups, preventative tool replacement, and comparatively low welding speeds restrict the application of FSW.…”
Section: Introductionmentioning
confidence: 99%
“…This simplicity has made it the most commonly used configuration in FSW despite the rough periodic surface structures and inferior mechanical fatigue properties [3,11]. Recent investigations are extensive and pointing thematic priorities such as weld seam properties of similar and dissimilar materials, varying probe/shoulder geometries, tool wear, and the interactions between tool and FSW setup [4,6,7,12,13].…”
Section: Introductionmentioning
confidence: 99%